Driving Employee Ecological Behavior through Responsible Leadership and Green Orchestration Innovation - Masyhuri; Tham Lam Nguyen; Qaisar Iqbal (Fundamental and Applied Management Journal, 2026)
This study aims to investigate how responsible leadership and green orchestration innovation influence employee ecological behavior, with environmental harmonious passion acting as a mediating mechanism. Using a quantitative approach, data were collected from 360 employees of banking institutions in East Java and analyzed using structural equation modeling. The results reveal that responsible leadership does not have a direct significant effect on employee ecological behavior; however, it significantly influences environmental harmonious passion. Green orchestration innovation demonstrates a positive effect on both environmental harmonious passion and employee ecological behavior. Furthermore, environmental harmonious passion significantly mediates the relationships between responsible leadership and employee ecological behavior, as well as between green orchestration innovation and employee ecological behavior. These findings indicate that leadership and innovation strategies are most effective in promoting ecological behavior when they foster employees’ intrinsic motivation and emotional attachment to environmental values. This study contributes to the literature by highlighting the importance of psychological mechanisms in sustainability-oriented leadership and innovation, particularly within the banking sector. Practically, the findings suggest that banking institutions should prioritize people-centered leadership and integrated green innovation strategies to strengthen employees’ commitment to environmental sustainability.